Higgs pair production as a signal of enhanced Yukawa couplings - Bauer, Martin; Carena, Marcela; Carmona, Adrián (Physical review letters, 2018)
We present a nontrivial correlation between the enhancement of the Higgs-fermion couplings and the Higgs pair production cross section in two Higgs doublet models with a flavor symmetry, with implications for LHC searches. This symmetry suppresses flavor-changing neutral couplings of the Higgs boson and allows for a partial explanation of the hierarchy in the Yukawa sector. After taking into account the constraints from electroweak precision measurements, Higgs coupling strength measurements, and unitarity and perturbativity bounds, we identify an interesting region of parameter space leading to enhanced Yukawa couplings as well as enhanced di-Higgs gluon fusion production at the LHC reach. This effect is visible in both the resonant and nonresonant contributions to the Higgs pair production cross section. We encourage dedicated searches based on differential distributions as a novel way to indirectly probe enhanced Higgs couplings to light fermions.